2022
DOI: 10.1002/esp.5504
|View full text |Cite
|
Sign up to set email alerts
|

Impact of upstream reservoirs on geomorphic evolution in the middle and lower reaches of the Yangtze River

Abstract: Intensive human activities in river basins have substantial effects on fluvial hydrological and morphological processes and developmental trends. In this study, we assessed the evolutionary characteristics and developmental trends of the fluvial morphological system of the Three Gorges Dam (TGD) downstream to understand the impacts of human activities on the fluvial hydrological–morphological system of the region. The results indicated that the Three Gorges Project (TGP) and other upstream cascade reservoirs p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…During the period 1956–2002, Songzikou, Taipingkou, Ouchikou (Guan), and Ouchikou (Kang) were cut off for 81, 83, 95, and 198 days, respectively, whereas during the period 2003–2021, this number increased to 178, 140, 180, and 271 days, respectively, an increase of 97, 57, 85, and 73 days, respectively. After the operation of the TGP, the Jingjiang reach in the middle reaches of the Yangtze River was eroded by the river channel (Yang, Zheng, et al, 2022b; Y. P. Yang, Zhou, et al, 2022), and the flow and low‐water level showed a downward trend (Chai et al, 2020; Y. Yang et al, 2017; Y. P. Yang, Zhang, Sun, Han, et al, 2018). Simultaneously, small‐scale erosion occurred predominantly at the three inlets and flood channels (Wei et al, 2022); however, offsetting the impact of the water level decline of the mainstream was difficult.…”
Section: Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the period 1956–2002, Songzikou, Taipingkou, Ouchikou (Guan), and Ouchikou (Kang) were cut off for 81, 83, 95, and 198 days, respectively, whereas during the period 2003–2021, this number increased to 178, 140, 180, and 271 days, respectively, an increase of 97, 57, 85, and 73 days, respectively. After the operation of the TGP, the Jingjiang reach in the middle reaches of the Yangtze River was eroded by the river channel (Yang, Zheng, et al, 2022b; Y. P. Yang, Zhou, et al, 2022), and the flow and low‐water level showed a downward trend (Chai et al, 2020; Y. Yang et al, 2017; Y. P. Yang, Zhang, Sun, Han, et al, 2018). Simultaneously, small‐scale erosion occurred predominantly at the three inlets and flood channels (Wei et al, 2022); however, offsetting the impact of the water level decline of the mainstream was difficult.…”
Section: Research Resultsmentioning
confidence: 99%
“…Following the construction of the TGR, the erosion of Dongting Lake led to an increase in the low‐water level and the depth of the waterway (M. Zhang et al, 2015). Subsequently, after the operation of the TGP, the volume of sediment entering the middle reaches of the Yangtze River has significantly reduced (Y. P. Yang, Zheng, Zhu, et al, 2022), causing strong erosion in the Jingjiang reach (Y. P. Yang et al, Zhou, et al, 2022). The first phase of the waterway improvement project in the Jingjiang reach increased the depth of the waterway from 2.9 m in 2002 to 3.5–3.8 m in 2018 (Yan et al, 2019; Y. Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…With the commissioning of the TGR and a series of cascade reservoirs in the upper Yangtze River, hydrological elements, such as the D f magnitude, temporal and spatial distribution, and the SSC entering the middle and lower reaches of the Yangtze River (MLYR) have changed, resulting in significant changes in the evolution of the riverbed downstream of the reservoirs 45 . The first and foremost change was a reduction in the flood peak.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure 2, a big flood occurred in 1998 at the Yangtze River resulting in a significant high sediment load. The sediment load decreased notably after 2013 at Qingxichang as sediment was trapped by cascade reservoirs at the upper Yangtze River and its tributaries (Jiang et al., 2023; Yang et al., 2023). The average trap efficiency of the TGD (i.e., the ratio of sediment trapped in the reservoir to the total sediment inflow) was 78% during 2003–2018 (Liu et al., 2022).…”
Section: Study Area and Water And Sediment Conditionsmentioning
confidence: 99%